Pengembangan Aplikasi Layanan Informasi Peninggalan Sejarah Peradaban dan Cagar Budaya berbasis Platform Android (Studi Kasus: Dinas Pariwisata, Kepemudaan, Olahraga dan Kebudayaan Kabupaten Nganjuk) - Arifandis Winata; Agi Putra Kharisma; Novanto Yudistira (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
History is a reconstruction of the past according to Prof. DR. Kuntowijoyo, almost every area has a history, as well as Nganjuk, a district that has a history in its past, as evidenced by the existence of historical relics such as temples, household tools, agricultural tools, vehicles, paintings, and sculptures which are archived in books by the Tourism Office, Youth, Sports and Culture Nganjuk. However, Nganjuk's history is not fully contained in the book because every discovery of a new historical relic takes a long process and time to update existing information. So, to facilitate the addition of information and explanation, an information service is used with the development of an Android-based mobile application to facilitate access both for the general public and for the Nganjuk Tourism, Youth, Sports and Culture Office. With the information service application, it is hoped that it can make it easier to find and update historical information quickly and easily. The application is developed with the Model-View-Presenter (MVP) architecture with the results of testing all functionality showing that the system is valid and the results of the usability test show an average above 80% which means the application is feasible to use, and can run on the Android operating system with a level SDK 16 to 29.